A reusable catalytic system for sulfide oxidation and epoxidation of allylic alcohols in water catalyzed by poly(dimethyl diallyl) ammonium/polyoxometalate. Issue 4 (10th November 2015) - Zhao, Wei; Yang, Chunxia; Cheng, Zhiguo; Zhang, Zhenghui
Abstract : An effective catalyst based on a polyoxometalate and a polymer has been developed for the oxidation of sulfides and allylic alcohols under mild conditions in water. Abstract : An effective catalyst based on a polyoxometalate and a polymer has been developed for the oxidation of sulfides and allylic alcohols under mild conditions in water. The synthetic procedure to form the catalyst and the separation of the products are convenient, and the system is reusable.